DIAGNOSIS OF DEEP VEIN THROMBOSIS IN THE LEG BY USING COLOUR CODED DUPLEX SONOGRAPHY - AMIN, MUHAMMAD AMJAD; KHAN, MUHAMMAD ZAFAR; KHAN, MANSOOR ALI; TARIQ, NASEER AHMAD (Journal of Ayub Medical College Abbottabad, 2001)
Background: Deep Vein Thrombosis (DVT) is regarded rare. Asia. There is no documentation of the incidence of DVT in Pakistan. Clinical diagnosis of Deep Vein Thrombosis is inaccurate. Venography is the most reliable method of diagnosis, but it has several disadvantages. Many non- invasive diagnostic methods have therefore been developed in the past decade. Of these only duplex sonography has comparable accuracy. Methods: We studied 100 cases of suspected DVT by using colour coded duplex sonography. We report the results of a prospective study in patients with suspected deep vein thrombosis evaluated by both colour coded Doppler sonography and venography. Conclusion: We conclude that colour coded duplex sonography is a highly accurate, simple, non-invasive method for detecting femoropoplitical thrombosis. Additional venography is not necessary. its value in diagnosing isolated calf vein thrombosis remains to be established.